AI Ethics and Responsible AI Development: Navigating the Ethical Landscape of Artificial Intelligence - V Khadake, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This in-depth article on the ethics and responsible development of artificial intelligence (AI) looks at how quickly AI technologies are changing society and how big those changes are. Ethical issues like bias, privacy, responsibility, and openness are looked at in detail. It outlines responsible AI development principles, encompassing fairness, human-centered values, and safety. It discusses practical strategies for implementing ethical AI practices, including diverse development teams and explainable AI techniques. The article examines applications of responsible AI across finance, recruitment, and healthcare. Finally, it looks at future directions for AI ethics, including regulatory frameworks, global collaboration, interdisciplinary research, and education initiatives. By addressing these crucial ethical challenges, the aim is to ensure AI technologies align with human values and benefit society as a whole.
Keywords: Artificial Intelligence Ethics; Responsible AI Development; AI Bias and Fairness; Data Privacy in AI; AI Accountability; Transparency